Isolation of aeromycoflora in the indoor environment of chawri bazar metro-railway station, Delhi, India - Nafis, Arshi; Sharma, Kavita (Recent Research in Science and Technology, 2012)
Air almost always contains spores, but the number and type of spores depend on the time of day, weather, season and geographical location. The aim of the study was to evaluate the prevalent species of airborne fungi in the indoor environment of the Chawri Bazar Metro-Railway Station, Delhi, India. Air sample was collected for four months within the interval of two weeks by means of gravitational settling method via Petri dishes with Potato Dextrose Agar (PDA) culture media. Those fungi colonies that formed after an incubation period of 3 to 5 days at 25 to 28°C were determined on the basis of micro and macro morphological characteristics. During the investigation period Aspergillus, Penicillium, Curvularia, Cladosporium, and Fusarium are reported as dominant fungal types. In this investigation, among fourteen spore types, Aspergillus niger was the most prevalent fungal genera followed by Aspergillus flavus and Penicillium sp. The results of this investigation appeared to be quite significant for taking corrective measures.